Bacterial direct-fed microbials fail to reduce methane emissions in primiparous lactating dairy cows - Jeyanathan, Jeyamalar (J Anim Sci Biotechnol, 2019)
Direct-fed microbials (DFM) are considered as a promising technique to improve animal productivity without affecting animal health or harming the environment. The potential of three bacterial DFM to reduce methane (CH(4)) emissions, modulate ruminal fermentation, milk production and composition of primiparous dairy cows was examined in this study. As previous reports have shown that DFM respond differently to different diets, two contrasting diets were used in this study. Eight lactating primiparous cows were randomly divided into two groups that were fed a corn silage-based, high-starch diet (HSD) or a grass silage-based, high-fiber diet (HFD). Cows in each dietary group were randomly assigned to four treatments in a 4 × 4 Latin square design. The bacterial DFM used were selected for their proven CH(4)-reducing effect in vitro. Treatments included control (without DFM) and 3 DFM treatments: Propionibacterium freudenreichii 53-W (2.9 × 10(10) colony forming units (CFU)/cow per day), Lactobacillus pentosus D31 (3.6 × 10(11) CFU/cow per day) and Lactobacillus bulgaricus D1 (4.6 × 10(10) CFU/cow per day). Each experimental period included 4 weeks of treatment and 1 week of wash-out, with measures performed in the fourth week of the treatment period. Enteric CH(4) emissions were measured during 3 consecutive days using respiration chambers. Rumen samples were collected for ruminal fermentation parameters and quantitative microbial analyses. Milk samples were collected for composition analysis. Body weight of cows were recorded at the end of each treatment period. Irrespective of diet, no mitigating effect of DFM was observed on CH(4) emissions in dairy cows. In contrast, Propionibacterium increased CH(4) intensity by 27% (g CH(4)/kg milk) in cows fed HSD. There was no effect of DFM on other fermentation parameters and on bacterial, archaeal and protozoal numbers. Similarly, the effect of DFM on milk fatty acid composition was negligible. Propionibacterium and L. pentosus DFM tended to increase body weight gain with HSD. We conclude that, contrary to the effect previously observed in vitro, bacterial DFM Propionibacterium freudenreichii 53-W, Lactobacillus pentosus D31 and Lactobacillus bulgaricus D1 did not alter ruminal fermentation and failed to reduce CH(4) emissions in lactating primiparous cows fed high-starch or high-fiber diets. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40104-019-0342-9) contains supplementary material, which is available to authorized users.